Assessing vaccination coverage in the European Union: is it still a challenge?. (August 2011) - Haverkate, Manon; D''Ancona, Fortunato; Johansen, Kari; van der Velden, Koos; Giesecke, Johan; Lopalco, Pier Luigi
Assessing vaccination coverage is of paramount importance for improving quality and effectiveness of vaccination programs. In this article, some of the different systems that are used for assessing vaccination coverage within and outside the EU are reviewed in order to explore the need for improving vaccination coverage data quality. All countries in the EU have implemented vaccination programs for children, which include vaccinations to protect against between nine and 14 infectious diseases. Collecting and assessing vaccination coverage regularly is part of such programs, but the methods used vary widely. Some quality issues are evident when data reported through administrative methods are compared with seroprevalence studies or other surveys. More thorough assessment of vaccination coverage and more effective information sharing are needed in the EU. A homogeneous system for assessing vaccination coverage would facilitate comparability across countries and might increase the level of the quality of both the national and local systems. Cooperative and coordinated responses to vaccine-preventable disease threats might be improved by better information sharing.